Flexible viruses structural disorder in viral proteins - Uversky, Vladimir N. (Wiley series in protein and peptide science, 2012)
"This book provides up-to-date information on experimental and computational characterization of the structural and functional properties of viral proteins, which are widely involved in regulatory and signaling processes. With chapters by leading research groups, the book features current information on the structural and functional roles of intrinsic disorders in viral proteomes. It systematically addresses the measles, HIV, influenza, potato virus, forest virus, bovine virus, hepatitis, and rotavirus as well as viral genomics. After analyzing the unique features of each class of viral proteins, future directions for research and disease management are presented"--